Disrupted Network Topology Contributed to Spatial Navigation Impairment in Patients With Mild Cognitive Impairment - Li, Weiping; Zhao, Hui; Qing, Zhao; Nedelska, Zuzana; Wu, Sichu; Lu, Jiaming; Wu, Wenbo; Yin, Zhenyu; Hort, Jakub; Xu, Yun; Zhang, Bing (Frontiers in Aging Neuroscience, 2021)
Impairment in spatial navigation (SN) and structural network topology is not limited to patients with Alzheimer's disease (AD), and can be detected earlier in patients with mild cognitive impairment (MCI). We recruited 32 MCI patients (65.91±11.33 years old) and 28 normal cognition patients (69.68±10.79 years old) in this study, all of whom underwent a computer-based battery of SN tests and diffusion-weighted and T1-weighted MRI. To evaluate the topological features of the structural network, we calculated the global efficiency, local efficiency, clustering coefficient, and shortest path length with GRETNA from weighted connectivity matrices based on DTI. We further analysed the correlation between SN accuracy and network topological properties. Compared with normal controls(NC), MCI subjects showed significantly decreased clustering coefficients in the left middle frontal gyrus, right rectus, right superior parietal gyrus and right inferior parietal gyrus; decreased shortest path length in the left paracentral lobule; and increased global efficiency in the right middle orbital frontal gyrus. Compared to normal controls, MCI subjects demonstrated worse egocentric navigation, which was indicated by a larger average total error. We observed a significantly positive correlation of the shortest path length in the left paracentral lobule with both the allocentric-egocentric average total error and the allocentric average total error. A decreased clustering coefficient in the right inferior parietal gyrus was associated with a larger allocentric navigation error. This study demonstrated network abnormalities, including global efficiency, clustering coefficient and shortest path length, mainly in the frontal and parietal gyri, that were associated with worse spatial navigation accuracy, which may provide new insight into the brain mechanism associated with SN impairment in MCI.